Movement behavior policies in the early childhood education and care setting: An international scoping review - Wenden, Elizabeth J.; Virgara, Rosa; Pearce, Natasha; Budgeon, Charley; Christian, Hayley E. (Frontiers in Public Health, 2023)
Background: Meeting 24-hour movement behavior guidelines for the early years is associated with better health and development outcomes in young children. Early childhood education and care (ECEC) is a key intervention setting however little is known about the content and implementation of movement behavior polices in this context. To inform policy development this international scoping review examined the prevalence, content, development and implementation of ECEC-specific movement behavior policies. Methods: A systematic literature search of published and grey literature since 2010 was conducted. Academic databases (EMBASE, Cinahl, Web of Science, Proquest, Scopus, EBSCO, PubMed) were searched. A Google search was undertaken and limited to the first 200 results. The Comprehensive Analysis of Policy on Physical Activity framework informed data charting. Results: Forty-six ECEC policy documents met inclusion criteria. Most policies originated in the USA, were subnational and developed with government, non-government organizations and ECEC end-users. Physical activity was specified in 59% (30-180 minutes/day), sedentary time in 51% (15-60 minutes/day) and sleep in 20% (30-120 minutes/day) of policies. Daily outdoor physical activity was recommended (30-160 minutes/day) in most policies. No policy permitted screen time for children <2 years, with 20-120 minutes/day for children >2 years. Most policies (80%) had accompanying resources but few provided evaluation tools (e.g., checklists; action plan templates). Many policies had not been reviewed since the publication of 24-hour movement guidelines. Conclusion: Movement behavior policies in the ECEC setting are often vaguely worded, missing a comprehensive evidence base, siloed in development and often not tailored for the ‘real world’. A focus on evidence informed ECEC-specific movement behavior policies proportionally aligned with national/international 24-hour Movement Behaviors Guidelines for the Early Years is needed.